Heparin-induced multiple electrode aggregometry is a promising and useful functional tool for heparin-induced thrombocytopenia diagnosis: Confirmation in a prospective study. (September 2013) - Galea, Vassiliki; Khaterchi, Amir; Robert, Francoise; Gerotziafas, Grigoris; Hatmi, Mohamed; Elalamy, Ismail
<x xml:space="preserve">Abstract</x> Heparin-induced thrombocytopenia (HIT) is a potentially lethal adverse effect of heparin therapy. Accurate and rapid HIT laboratory diagnosis when HIT is suspected is crucial. The combination of an immunological assay with a functional test improves the accuracy of HIT, but functional assays are currently limited to a few laboratories. Multiplate® analyzer (Dynabyte, Munich, Germany) is a practical, semi-automated and easy-to-perform platelet aggregation assay. The aim of this study is to explore whether heparin-induced platelet aggregation in whole blood assessed by Multiplate® (Heparin-induced multiple electrode aggregometry, HIMEA) can replace platelet aggregation test (PAT) in platelet-rich plasma. For this purpose, HIMEA performance in HIT diagnosis was prospectively evaluated. HIMEA and PAT were compared to serotonin-release assay (SRA) in 200 well-characterized consecutive patients suspected for HIT. HIMEA was found to be more sensitive (81% vs. 76%) and more specific (99% vs. 96%) than PAT compared to SRA. Both tests showed a high negative predictive value while HIMEA had a better positive predictive value. HIMEA has overall better performance characteristics than PAT for the detection of HIT platelet-activating antibodies. The combination of an immunological assay with HIMEA could be a feasible option in non-specialized laboratories for HIT diagnosis optimization.